Trabecular meshwork gene expression after selective laser trabeculoplasty. - Alberto Izzotti (Public Library of Science (PLoS), 2011)
Background Trabecular meshwork and Schlemm's canal are the tissues appointed to modulate the aqueous humour outflow from the anterior chamber. The impairment of their functions drives to an intraocular pressure increase. The selective laser trabeculoplasty is a laser therapy of the trabecular meshwork able to decrease intraocular pressure. The exact response mechanism to this treatment has not been clearly delineated yet. The herein presented study is aimed at studying the gene expression changes induced in trabecular meshwork cells by selective laser trabeculoplasty (SLT) in order to better understand the mechanisms subtending its efficacy. Methodology/principal findings Primary human trabecular meshwork cells cultured in fibroblast medium underwent selective laser trabeculoplasty treatment. RNA was extracted from a pool of cells 30 minutes after treatment while the remaining cells were further cultured and RNA was extracted respectively 2 and 6 hours after treatment. Control cells stored in incubator in absence of SLT treatment were used as reference samples. Gene expression was evaluated by hybridization on miRNA-microarray and laser scanner analysis. Scanning electron microscopic examination was performed on 2 Trabecular meshwork samples after SLT at 4(th) and 6(th) hour from treatment. On the whole, selective laser trabeculoplasty modulates in trabecular meshwork the expression of genes involved in cell motility, intercellular connections, extracellular matrix production, protein repair, DNA repair, membrane repair, reactive oxygen species production, glutamate toxicity, antioxidant activities, and inflammation. Conclusions/significance SLT did not induce any phenotypic alteration in TM samples. TM is a complex tissue possessing a great variety of function pivotal for the active regulation of aqueous humour outflow from the anterior chamber. SLT is able to modulate these functions at the postgenomic molecular level without inducing damage either at molecular or phenotypic levels.